2020
DOI: 10.1152/physrev.00038.2018
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotides and P2 Receptors in Renal Function

Abstract: The understanding of the nucleotide/P2 receptor system in the regulation of renal hemodynamics and transport function has grown exponentially over the last 20 yr. This review attempts to integrate the available data while also identifying areas of missing information. First, the determinants of nucleotide concentrations in the interstitial and tubular fluids of the kidney are described, including mechanisms of cellular release of nucleotides and their extracellular breakdown. Then the renal cell membrane expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 578 publications
(806 reference statements)
0
65
0
1
Order By: Relevance
“…Studies using combined techniques, such as selective antagonists, or tissue selective or global P2Y receptor subtype deficient mice, helped to elucidate the role of these receptors in most aspects of the cardiovascular system. Also, the role of P2YRs in renal function was recently reviewed (Vallon, Unwin, Inscho, Leipziger, & Kishore, 2019).…”
Section: P2y Receptors In the Cardiovascular Systemmentioning
confidence: 99%
“…Studies using combined techniques, such as selective antagonists, or tissue selective or global P2Y receptor subtype deficient mice, helped to elucidate the role of these receptors in most aspects of the cardiovascular system. Also, the role of P2YRs in renal function was recently reviewed (Vallon, Unwin, Inscho, Leipziger, & Kishore, 2019).…”
Section: P2y Receptors In the Cardiovascular Systemmentioning
confidence: 99%
“…It has been shown that inhibiting P2 receptors rapidly enhances ENaC activity [16]. Experimental evidence documents the expression and functionality of P2Y2 and P2Y4 receptors in the collecting duct [11,13,16,35].…”
Section: Discussionmentioning
confidence: 92%
“…Data implicate an important role for purinoceptors (P2 receptors) in controlling urinary Na + excretion [10,11]. P2 receptors are classified into ligandgated ion channels, P2X1-7, and G protein-coupled receptors, P2Y1,2,4,6,11-14 receptors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that inhibiting P2 receptors rapidly enhances ENaC activity [16]. Experimental evidence documents the expression and functionality of P2Y 2 and P2Y 4 receptors in the collecting duct [11,13,16,40]. P2Y 2 knockout mice are hypertensive, possibly due to ENaC hyperactivity leading to enhanced renal Na + reabsorption [14,16].…”
Section: Discussionmentioning
confidence: 99%